PENGARUH TENAGA KERJA DAN MODAL USAHA MIKRO TERHADAP PENDAPATAN PELAKU USAHA DI KECAMATAN AMPEK ANGKEK KEBUPATEN AGAM - Rahmat Syawal Putra; Amsah Hendri Doni (BORJUIS: JURNAL OF ECONOMY, 2024)
The framework of this research is to see how much the aspects-views that influence the income of business actors through micro business actors located in the Ampek Angkek District area, although in terms of activity power and business capital have been managed well, but the income of business actors has not been managed well. This research intends to identify the impact of activity power and micro business capital on the income of business actors. Information is combined through the selection of basic information. This type of research is descriptive quantitative. After that, it was tried through a procedure that includes information prerequisite experiments consisting of (Normality Experiment and Reliability Experiment), then Classical assumption experiments consisting of (Autocorrelation Experiment, Homogeneity Experiment and Multicollinearity Experiment, and Heteroscedasticity Experiment) then multiple linear regression experiments, then Coefficient of Certainty Experiment, then Assumption Experiment consisting of (partial experiments and simultaneous experiments). To analyze using the SPSS 26.0 Application. The basis used in this study uses the Income philosophy. Based on the results of the tests that were tried, the following conclusions can be put forward: 1) Activity Power has a positive and significant effect on the Income of Micro Business Actors in Ampek Angkek District in 2023 with a result of 0.000≤0.05, so the result of H0 is rejected and H1 is obtained. 2) Effort Capital on Income of Micro Business Actors in Ampek Angkek District in 2023 with a result of 0.000≥0.05, so the result of H0 is rejected and H1 is obtained. 3) Simultaneously, Activity Power and Effort Capital have a significant effect on Income of Business Actors with a result of 0.000≥0.05, so the result of H0 is rejected and H1 is obtained. The analysis of the findings shows that Activity Power and Micro Business Capital have a significant effect on Income of Business Actors in Ampek Angkek District.